(untitled) (Journal of Tropical Pharmacy and Chemistry, 2012)
This study aims to determine the content of secondary metabolites and antibacterial power crude extract copper leaf meranti (Shorea leprosula Miq.) against Staphylococcus aureus and Escherichia coli. Antibacterial power is determined by the size of inhibition zone formed using paper disc diffusion method of Kirby-Bauer. The research design using a completely randomized design (CRD), with a concentration of 6 treatments and 4 replication for each type of bacteria. Variations in the concentration of a given treatment consisting of 0%, 3.75%, 7.5%, 11.25%, 15%, and chloramphenicol (positive control). The results shown that crude extract copper leaf meranti (Shorea leprosula Miq.) contain secondary metabolites such as alkaloids, saponins, triterpenoids, flavonoids, phenols and antibacterial power against Staphylococcus aureus and Escherichia coli, with the relatively strong antibacterial category. Anova analysis showed that the value of F count = 41,190 with sig = 0.000 <0.05, which means that H0 is rejected, in other words, treatment factors meranti copper leaf crude extract with various concentrations of 3.75%, 7.5%, 11, 25%, and 15%. different significantly affect the bacterial inhibition zone for S. aureus. The result same effect shown onE. coli demonstrated the value Fcount = 81, 236 with sig = 0.000 <0.05. These results demonstrate the influence of crude extract of leaf meranticopper very significantly to the growth of bacteria S. aureus and E. coli. At S.aureus, treatment concentration of 3.75%, 7.5%, 11.25%, and 15%yielding different significant of inhibition zone. In the E.colibacterial, treatment concentration of 3.75%, 7.5%, 11.25%, and 15% yielding different significant of inhibition zone.Best concentration as antibacterial S.aureus and E.coli have been shown on providing the lowest treatment concentration (3.75%), which shows the power antibacterial properties not significantly different from the concentration on it.